(untitled) (Revista de Investigaciones Universidad del Quindío, 2016)
This project presents the results of introducing a speed control by using ultrasound and accelerometer sensors to detect objects associated to a fuzzy controller to prevent collisions in enclosed spaces. By implementing this anticollision model, indoor navigation of aerial robots becomes safer.